Laser on Silicon. - Moore, S.K (IEEE spectrum)
Silicon is not a natural for producing and manipulating light. Nevertheless, Intel and Luxtera each have been able to produce silicon versions of optoelectronic components by binding a light emitter made from indium phosphide to a silicon laser cavity. The key was in making a kind of glass glue, a thin layer of oxidized material, on both the indium-phosphide light emitter and the silicon laser and then bonding them together. Applying a voltage to the indium phosphide device produces light that passes through the glass into the silicon